Employing Indigenous Methodologies to Understand Women's Perceptions of HIV, Health, and Well-being in Quebec, Canada. Issue 2 (August 2020) - O'Brien, Nadia; Martin, Carrie; Peltier, Doris; Kaida, Angela; Becker, Marissa; Bourassa, Carrie; Gervais, Laverne; Bruce, Sharon; Loutfy, Mona; de Pokomandy, Alexandra
Guided by an Indigenous Methodology and a participatory research approach, we explored the experiences and priorities of Indigenous women living in Quebec regarding HIV prevention and care, overall health, and well-being. We drew from our research process to identify recommendations for conducting research with Indigenous women. These lessons include: (1) incorporating culturally adapted methods (e.g., sharing circles, arts, ceremony) facilitated participants' safety and comfort; (2) conducting numerous workshops was valuable in building trust; and (3) validating findings with participants was essential to ensuring that the knowledge, experiences, and priorities of Indigenous women were respected. Our research findings regarding the care needs and priorities of women emphasize the importance of peer-led groups, culturally rooted healing strategies, accessible harm reduction, and social supports. Participatory research, led by members of the communities concerned, imbues the research with local knowledge and wisdom, which ensures the relevance of the research, the appropriateness of its conduct, and enables its overall success.